Serum cardiac and inflammatory biomarker levels following chemotherapy among female patients with breast cancer attending at Tikur Anbessa Specialized Hospital, Addis Ababa, Ethiopia - Muluabay Getie; Biset Asrade Mekonnen; Daniel Seifu; Yonas Mulugeta; Solomon Tebeje; Chernet Tafere; Asmare Amuamuta (BMC Cancer)
Abstract Background Chemotherapy is a well-established therapeutic approach for several malignancies, including breast cancer (BCa). However, the clinical efficacy of this drug is limited by cardiotoxicity. Assessing multiple cardiac biomarkers can help identify patients at risk of adverse outcomes from chemotherapy. Objective To evaluate changes in serum cardiac and inflammatory biomarker levels following chemotherapy among female patients with BCa attending at Tikur Anbessa Specialized Hospital, Addis Ababa, Ethiopia. Methods An experimental study design was used. Forty patients with breast cancer were selected using a convenience sampling method. After obtaining informed consent, 40 paired samples (40 samples before chemotherapy and 40 matched samples after three cycles of chemotherapy) were collected between May 2018 and March 2019. An Elecsys 2010 Troponin-T immunoassay analyzer was used to measure serum levels of cardiac troponin T (cTnT), creatinine kinase-myocardial band (CK-MB), C-reactive protein (CRP), and R and D systemic luminex performance assays were used to measure serum Interleukin-6 (IL-6) and Tumor Necrosis Factor-alpha (TNF- α). Data were analyzed using the SPSS version 23 package, and a p-value < 0.05 was considered statistically significant. Results Among female patients with BCa receiving chemotherapy, 20%, 15%, and 35% of patients had elevated cTnT, CK-MB, and CRP levels, respectively, after three cycles of chemotherapy. In contrast, 15% of patients had baseline elevated CRP levels compared with their respective cutoff values. The mean serum cTnT, CK-MB, CRP, and TNF-α levels significantly increased (p < 0.05) compared with their respective baseline values. However, the IL-6 levels at baseline and after chemotherapy were not significantly different. Conclusion This study revealed significant increases in cardiac and inflammatory biomarkers following chemotherapy among female patients with breast cancer in the study area. Therefore, cardiac biomarkers and echocardiography findings were used to assess functional abnormalities and treatment outcomes.